Estimativa da área foliar de Euphorbia heterophylla - Duarte, D. J. [UNESP] (2009)
Leaf area estimate may contribute to understand the relationships of interference among weeds and crops. The objective of this research was to obtain a mathematical equation to estimate the leaf area of Euphorbia heterophylla based on linear measures of the leaf blade. Correlation studies were carried out using the real leaf area and leaf length (C) and the maximum leaf width (L) of 200 leaf blades which were collected from several agroecosystems at Universidade Estadual Paulista in Jaboticabal, SP, Brazil. The evaluated statistic models were: linear Y = a + bx; simple linear Y = bx; geometric Y = ax b; and exponential Y = ab x. All of the evaluated models can be used for E. heterophylla leaf area estimation. The simple linear regression model is suggested using C*L and taking the linear coefficient equal to zero. Thus, an estimate of the leaf area of E. heterophylla can be obtained using the equation Af' = 0.6816*(C*L).